ANALISIS KETERAMPILAN BERTANYA LANJUT GURU PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM - Nurhaty Purnama Sari (CAHAYA PENDIDIKAN, 2020)
This study aims to determined the questioning skills of elementary school teachers, especially in science material. This research conducted in three public elementary schools in Batam. It was using qualitative descriptive methods with data collection were observation, interviews and documentation. From the research results, it was found that the teacher was good category in performing advanced questioning skills. The questioning skills done by the teacher was changing the demands of the cognitive level in answering questions, from the lowest level to the highest level such as understanding, applying, analyzing, synthesizing, and evaluating and arranging the order of questions, starting from the simplest questions. followed by questions with complex questions. In the study, it was found that the teacher had not yet performed further questioning skills in the section using tracer questions with various techniques